The Importance of Awareness of the Dangers of Drugs for the Young Generation in Lhokseumawe City - Arkan, M. Syafy (Jurnal Transparansi Publik (JTP), 2024)
The abuse of narcotics, psychotropics, and other addictive substances (NARCOTIC) is a serious problem that threatens Indonesia's young generation. Narcotics can cause physical, psychological, and social damage that harms individuals and society. This study aims to understand the definition of narcotics, their types, factors that cause abuse, negative impacts caused, and preventive efforts that can be made to overcome this problem. The results of the study show that individual and environmental factors play a major role in increasing the risk of drug abuse. Therefore, joint efforts are needed between families, communities, and the government to prevent narcotics abuse. Education, strict supervision, and stricter law enforcement need to be improved to protect Indonesia's young generation from the dangers of narcotics.